2013
DOI: 10.1186/1471-244x-13-168
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on reasons for non-adherence to medication in persons with schizophrenia in Ethiopia: a qualitative study of patients, caregivers and health workers

Abstract: BackgroundLevels of non-adherence to antipsychotic medication in persons with schizophrenia in rural African settings have been shown to be comparable to those found in high-income countries. Improved understanding of the underlying reasons will help to inform intervention strategies relevant to the context.MethodsA qualitative study was conducted among persons with schizophrenia (n = 24), their caregivers (n = 19), research field workers (n = 7) and health workers (n = 1) involved in the ongoing population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 47 publications
(61 reference statements)
4
97
1
3
Order By: Relevance
“…Non-adherence to medication was associated with heightened risk of violent victimization in our study. Although people with SMI in our study did not have to pay for antipsychotic medication, the inaccessibility of centralized psychiatric services and influence of poverty meant that non-adherence was commonplace and likely to be associated with poorly controlled symptoms (Teferra et al, 2013). A fourth possible explanation relates to stigma.…”
Section: Violent Victimizationmentioning
confidence: 90%
“…Non-adherence to medication was associated with heightened risk of violent victimization in our study. Although people with SMI in our study did not have to pay for antipsychotic medication, the inaccessibility of centralized psychiatric services and influence of poverty meant that non-adherence was commonplace and likely to be associated with poorly controlled symptoms (Teferra et al, 2013). A fourth possible explanation relates to stigma.…”
Section: Violent Victimizationmentioning
confidence: 90%
“…The concept of tolerability might need a different approach and more careful analysis. In an earlier medication non-adherence study from the same population, factors such as poverty and family support were the most important reasons for non-compliance compared to tolerability indicating that there are more salient factors that might need further study (Teferra et al, 2013). Overall, medications in our cohort were well tolerated, with a relatively low rate of tardive dyskinesia (4.2%).…”
Section: Discussionmentioning
confidence: 58%
“…Prior studies that have noted the significant predictors of medication compliance were insight level of schizophrenia. This view is supported in prior explorative qualitative studies of purposively selected PDwS, where it was found that a myth associated with mental illness may have interfered with PDwS taking their prescribed medication [11].…”
Section: Discussionmentioning
confidence: 68%